(untitled) (International Journal of Engineering and Computer Science, 2016)
The number of peoples who rely on internet for information seeking is doubling in every seconds.as the information produced by the internet is huge it have been a problem to provide the users relevant information.so the developers developed algorithms for identifying users nature from their clickstream data and there by identifying what type of information they like to receive as an answer for their search. Later they named this process as Web Personalization. As a result of web personalization the users are looped Eli pariser an Internet Activist named this loop as “Filter Bubble”. This preliminary work explores filter bubble, its pros and cons and techniques to burst filter bubble